Pendampingan Pemasaran Potensi Pariwisata Pagaralam Untuk Kawasan Timur Tengah - Muhammad walidin (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2021)
Community Service with the theme Marketing the Potential Tourism of Pagaralam for the Middle East people is aimed to advocate the public to be aware of tourism and to become independent tourism ambassadors for their own region. The team from the Arabic Language and Literature Study Program collaborated with the community represented by the academic community of the Al-Azhar Islamic Boarding School to develop a social media-based tourism marketing pattern (Youtube). This process begins with brainstorming, composing a narrative text, translating text into Arabic, taking pictures and video, editing, and downloading video to Youtube. The result of the program is the appearance of a short video in Arabic as a form of marketing the potential tourism of Pagaralam to the Middle East people.